Federalism and accountability with distorted election choices - Sebastian G. Kessing (Center for Economic Studies and ifo Institute (CESifo), 2009)
Random factors such as bad weather or exogenous economic shocks affect the re-election of politicians and can reduce accountability. Such distorted election choices interact with the architecture of government. Contrasting centralized with decentralized political systems, this study shows that centralization is likely to result in higher accountability if election choices are subject to small random distortions. Furthermore, equity and efficiency arguments for uniform policies in centralized systems are derived as these are likely to result in the better overall performance of politicians and in more equal performance across regions.
Keywords: H73; D72; 330; accountability; federalism; decentralization; retrospective voting; Condorcet Jury Theorem; Föderalismus; Zentralstaat; Wiederwahl; Vergleich; Abstimmungsparadoxon; Theorie